Speech-language pathologists' responses on surveys on vocational stereotyping (role entrapment) regarding people who stutter. - Swartz E; Gabel R; Hughes S; Irani F (Contemporary Issues in Communication Science & Disorders)
Purpose: The purpose of this research study was to explore whether speech-language pathologists (SLPs) exhibit vocational stereotyping (role entrapment) toward people who stutter (PWS). Also, the effects of certain educational and professional experiences on the reports made by SLPs were examined. Method: The Vocational Advice Scale (VAS; R.M. Gabel, G. Tellis, & M.T. Althouse, 2004), which is a scale with 43 careers, was completed by 158 SLPs. A demographic and open-ended questionnaire was also completed by the SLPs to identify factors that influenced their choices on the VAS. Results: The results indicated the presence of role entrapment for only 2 of the careers on the VAS -- attorney and speech pathologist -- which were perceived to be less advisable or appropriate for males who stutter (MWS). This finding provides limited support for the notion that PWS suffer from role entrapment. Examination of the open-ended questions revealed that some SLPs would be supportive of MWS in various types of careers, but others commented on how stuttering would negatively affect the career choices of MWS or made general comments about the careers. Conclusion: Vocational stereotyping was found in only 2 out of 43 careers assessed in the study. Thus, it appears that stuttering did not lead to reports of role entrapment by this group of SLPs. Additionally, the total number of PWS whom the SLPs had treated in their career and the number of courses the SLPs had taken in stuttering had no effect on the participants' responses. However, participants who had engaged in professional readings in stuttering were more likely to provide positive advice to MWS for 2 of the careers. Future research might consider using different research approaches, including qualitative and mixed methods approaches, when studying role entrapment by SLPs. These methods might allow for a deeper understanding of this phenomenon.